The Use of Azolla microphylla in The Ration on Feed Consumption, Body Weight Gain, and Feed Conversion Ratio in Male Magelang Ducks (Anas platyrhinchos) - Lilis Hartati; Syaiful Iqbal; Mohamad Haris Septian; Tri Puji Rahayu; Nur Hidayah (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
The study aimed to determine feed consumption, body weight gain, and feed conversion of male Magelang ducks with the addition of Azolla microphylla in the ration. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. In each replication, there were 2 male Magelang ducks aged 5 weeks ( weight average is 747,18±103,9 g) and reared for 7 weeks. The treatment consisted of P0 control diet without Azolla microphylla substitution, P1 control diet + Azolla microphylla 10%., P2 control diet + Azolla microphylla 15%., and P3 control diet + Azolla microphylla 20%. Data collected included feed consumption, body weight gain, final body weight, and feed conversion. The data obtained were analyzed by analysis of variance (ANOVA), followed by Duncan's test. The addition of Azolla microphylla up to 20% had no significant effect on feed consumption (average 4706.17 ± 27.89 g), daily body weight gain (average 13.18 ± 1.65 g), and feed conversion (average 7. 38 ± 0.95), but significantly different in final body wight, the addition of Azolla microphylla up to levels of 15% and 20% reduced the final body weight of male Magelang ducks. The conclusions of this study were the addition of Azolla microphylla in the ration up to 20% did not affect feed consumption, daily body weight gain and feed conversion, but the addition of Azolla microphylla above 10% reduced the final body weight of male Magelang ducks. Substitition Azolla microphyla in Magelang duck male could be given up to 10% level.